Evaluation of genetic variants related to lipid levels among the North Indian population - Walia, Gagandeep Kaur; Panniyammakal, Jeemon; Agarwal, Tripti; Jalal, Ruchita; Gupta, Ruby; Ramakrishnan, Lakshmy; Tandon, Nikhil; Roy, Ambuj; Krishnan, Anand; Prabhakaran, Dorairaj (Frontiers in Genetics, 2024)
Background: Low and middle income countries like India that are rapidly undergoing urbanization have a huge unaddressed burden of cardiometabolic conditions. Indians are known to have high levels of triglycerides and low levels of HDL-C along with moderately higher levels of LDL-C. The genome-wide findings from western populations need to be validated in Indian context for better understanding of underlying etiology of dyslipidemia in India. We aim to validate 12 genetic variants of lipid levels among rural and urban Indian population and derive unweighted and weighted genetic risk scores (uGRS and wGRS) for lipid levels among Indian population .Methods: Assuming additive model of inheritance, linear regression models adjusted for all the possible covariates were run to examine the association of 12 genetic variants for total cholesterol, triglycerides, HDL-C, LDL-C and VLDL-C among 2117 rural and urban Indian participants. The combined effect of validated loci was estimated by allelic risk scores, unweighted and weighted by their effect sizes. The wGRS for triglycerides and VLDL-C was derived based on four associated variants (rs174546 at FADS1, rs17482753 at LPL, rs2293889 at TRPS1, rs4148005 at ABCA8, rs4420638 at APOC1) which was associated with 36.31 mg/dL elevated triglycerides and VLDL-C (β=0.95, SE=0.16, p<0.001). Similarly, every unit of combined risk score (rs2293889 at TRPS1 and rs4147536 at ADH1B) was associated with 40.62 mg/dL higher total cholesterol (β=1.01, SE=0.23, p<0.001) and 33.97 mg/dL higher LDL-C (β= 1.03, SE =0.19, p<0.001) based on its wGRS (rs2293889 at TRPS1, rs4147536 at ADH1B, rs4420638 at APOC1 and rs660240 at CELSR2). The wGRS derived from five associated variants (rs174546 and FADS1, rs17482753 at LPL, rs4148005 at ABCA8, rs4420638 at APOC1 and rs7832643 at PLEC) was associated with 10.64 mg/dL lower HDL-C (β= -0.87, SE =0.14, p<0.001).We confirm the role of eight GWAS loci related to different lipid levels in Indian population and demonstrate the combined effect of variants for lipid traits among Indians by deriving the polygenic risk scores. Similar studies among different populations are required to validate the GAS loci and effect modification of these loci by lifestyle and environmental factors related to urbanization.